A Pediatric Strategy for the Next Phase of the SARS-CoV-2 Pandemic - Danilo Buonsenso; Danilo Buonsenso; Danilo Buonsenso; Piero Valentini; Piero Valentini; Umberto Moscato; Umberto Moscato; Walter Ricciardi; Walter Ricciardi; Walter Ricciardi; Damian Roland; Damian Roland (Frontiers Media S.A., 2020)
Although the first wave of the SARS-CoV-2 pandemic relatively spared children, the next winter season will put a strain on health systems including pediatric services. Clinical staff managing children will need to deal not only with suspected cases of COVID-19, but also with the classic infectious agents that involve children during cold seasons. It will be necessary for physicians, institutions, policy makers, and families to prepare themselves for difficulties of this phase of the pandemic. Otherwise, the same problems experienced during the first wave of SARS-CoV-2, including shortages of human resources, personal protective equipment, and uncertainty, will be exacerbated by significant issues in hospital capacity. Here we highlight the potential role of improved vaccination services, school reorganization, home-outpatient-inpatients flows and telemedicine services in order to face the coming winter season.